Drug dependence and suicide, a growing problem: Farmacodependencia y suicidio, una problematica creciente | 药物依赖与自杀：一个日益严重的问题 - Leon Soto, Hector (2024)
Both nationally and internationally, drug dependence and suicide are problems with a high prevalence rate and in recent years have had an upward trend, bringing with them multiple social and health consequences. The relationship between drug dependence and suicide is statistically significant, with drug-dependent patients having a risk up to six times higher of attempting suicide compared to the general population. Therefore, it is important to know the risk factors associated with suicidal behavior in drug-dependent patients, in order to improve the prevention, treatment and prognosis of both problems. Although it is true that many of the risk factors associated with suicidal behavior are already known, these factors in the context of drug-dependent patients are still a subject that has not been investigated as much, and particularly at the national level, the variability of the factors according to the different regions, multiculturalism, socioeconomic strata, etc., are not taken into account. Therefore, it is recommended to increase the research budget, emphasizing on the variables and populations already mentioned, in order to have better qualified health personnel in the problem in question.